Cruzamento dialélico parcial entre linhagens endogâmicas de milho - Nardino, Maicon (2013)
Diallel are important to predict the best combinations between different heterotic groups of maize inbred lines, as well as knowledge of the associations between traits. The aim of this study is to estimate the combining ability among inbred lines by partial diallel analysis for identification of gene action involved in the expression of traits and prediction and identification of the best combinations of direct and indirect relations between genetic and phenotypic morphological traits on yield components . The strains used in partial diallel cross of the two heterotic groups are from the company KSP Seeds Ltda.. The tests were conducted based on crosses with partial diallel mating scheme, using 15 strains as the female parent and eight strains as male parent. The tests were conducted in five environments, in randomized complete block design with three replications. The variables analyzed were: stem diameter (DC), leaf angle (AF), tassel length (CP), distance from the last node of the stem to the first branch of the tassel (DUN), distance from the flag leaf to the first branch tassel (CFB), number of primary branches on the main stem of the tassel (NR), number of secondary branches in the tassel (NRS), leaf area (AFT), thousand grain weight (MMG) and grain yield. Group I estimates of lineages 15 and 4, 3 and 4 group II are favorable grain yield by CGC. The traits tassel length, distance from the last node of the flag leaf and the first branch of the tassel, the best combinations for CPB are 1-3 , 2-4 , 3-3 , 4-4 , 7-3 , 8-3 , 9-3 , 10-3 , 10-4 , 11-4 , 12-4 , 14-3 and 15-4 . The junctions promising for increased yield are 1-1 , 1-4 , 2-3 , 3-1 , 3-4 , 4-3 , 4-6 , 4- 7 , 5-3 , 5-4 , 6-3 , 6-4 , 7-4 , 8-4 , 9-4 , 10-5 , 11-3 , 12-3 , 14-4 , 15-2 , 15-5 and 15-8 . Among the most promising crosses for CEC at least two parents have high CGC. The distance from the last node to the first branch of the tassel, length and number of tassel branches negatively affect the yield estimates for linear phenotypic and genotypic methods. The distance from the last node to the first branch of the tassel negatively influences the performance and should be considered in the criteria for strain selection. Selections for smaller leaf angle and greater stem diameter and mass of a thousand grains appear to be favorable for the increase of grain yield in maize.